Hybridization Effect on Crashworthiness Parameters of Natural Composite - Salim Hamza, Sabah; Ismail, Al Emran; Yuhazri, M. Y.; Ariffin, Ahmad Hamdan; Hameed Sultan, Mohamed Thariq (Frontiers in Materials, 2021)
The use of metallic materials in automotive industry lead to increased fuel consumption and cost, so trends are starting to use lighter and cheaper materials. In automotive applications, fibres are used in composites due to they are stronger, stiff and lighter than bulk materials, as well as achieving higher energy absorbing compared to metallic materials. The purpose of this work is to study the potential utilizing of natural fibres in the crash energy absorbing applications. the experimental procedures (The principle of a combination of manual layup and vacuum bladder technique) was applied to search the influence of utilizing jute fibre mat on crashworthiness parameters of composite materials with other kinds of fibres such as woven glass fibre reinforced epoxy composites. The study involved corrugated composite tubes with three layers of jute and hybrid glass-jute/epoxy material have been tested in uniaxial quasi-static crush conditions at speed 10 mm/min. The results exhibit that the tube of jute fibre was somewhat lower than synthetic fibres, but the substitution of one layer of jute fibre with one layer of glass fibre resulted in an improvement in the crashworthiness parameters. As hybrid jute-glass was used, the best result was obtained, where energy absorption and specific energy absorption are improved by 17.75% and 25.122%, respectively.